(untitled) (Estudios humanísticos. Geografía, historia y arte, 1999)
This article uses a relation of secular benefices subscribed by bishop Diego Romano in 1591 as its documentary base. This report and information prepared by the same prelate in 1582 is analyzed to take a first look at the secular clergy of Tlaxcala: their training, origins, and knowledge of indigenous languages at the end of the sixteenth century.